PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN KECERDASAN SOSIAL TERHADAP SIKAP ETIS MAHASISWA AKUNTANSI - Andri Aji Bayu Pangestu, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2019)
The purpose of this study is to analyze the influence of intellectual intelligence (IQ), emotional intelligence (EQ), spiritual intelligence (SQ) and social intelligence (SoQ) on the accounting student's ethical attitude. Types of data use qualitative data and quantitative data. Data source uses primary data and secondary data. Collection techniques using questionnaires. The sampling technique used purposive sampling and samples of 83 respondents. Data analysis techniques use classical assumption test, multiple linear regression analysis, F test, t test, and test of coefficient of determination. The result of this research is intellectual intelligence have no significant positive effect on accountant's ethical attitude of accountant. Emotional intelligence negatively affects no significant effect on the ethical attitude of accounting students. Spiritual intelligence has a positive and significant influence on the ethical attitude of accounting students. Social intelligence positively insignificant effect on the ethical attitude of accounting students.Keywords: IQ, EQ, SQ, SoQ, Ethical Attitude